Experimental study on gas-liquid-liquid three-phase flow patterns and the resultant pressure drop in a horizontal pipe upstream of the 90Â° bend - Yaqub, M.W. (Elsevier Ltd, 2020)
The use of 90Ë bend for diversion of flow in different orientations is widespread. The current study is focused on the effect of 90Ë bend on gas-oilâwater three-phase flow in an upstream horizontal pipe. The diameter of the test section is 0.1524 m, and (R/d) ratio of the bend is 1. The ranges of superficial velocities of gas, oil, and water were 0.5â5, 0.08â0.36, and 0.08â0.36 m/s, respectively. The observed gasâliquid flow patterns are slug, pseudo-slug, stratified wavy, stratified roll wave, and stratified flow. The oil and water were observed to be flowing as a separate, partially mixed, and fully mixed liquid. Flow regime maps have been plotted to analyze the transition of flow patterns. The variation in pressure drop with the flow patterns has been studied. The experimental data has been used to develop pressure drop prediction correlation and the comparison with experimental results showed good agreement. Â© 2020 Elsevier Ltd